Why being there is not enough: organized proximity in place-based philanthropy - Glückler, Johannes; Ries, Martina (The service industries journal, 2012)
Philanthropy is gaining momentum in European society. Wealthy individuals and foundations are a growing source of financial benevolence. This paper explores the role of two concepts of proximity for obtaining access to philanthropic resources. First, geographical proximity refers to physical co-presence (‘being there’). It stresses the immediacy and serendipity of social interaction as facilitators of philanthropic support. In contrast, organized proximity refers to a network logic (‘being connected’) and emphasizes strategies of cooptation. Based on a multi-method case study in the city of Heidelberg, the paper finds philanthropy to be primarily place-based. Being there, however, is an insufficient condition since there is strong incidence that local organizational interlocks between advisory boards enhance the attraction of donations towards the social realm of academia.